Engaging complexity theory to explore partnership structures: Te Tiriti o Waitangi/The Treaty of Waitangi as a structural attractor for social innovation in Aotearoa-New Zealand. Issue 2 (4th August 2021) - Lythberg, Billie; Newth, Jamie; Woods, Christine
Abstract : Purpose: The purpose of this paper is to explore how a complexity informed understanding of Indigenous–settler relationships helps people to better understand Indigenous social innovation. To do this, this paper uses the attractor concept from complexity thinking to explore both the history and possible futures of Indigenous Maori social innovation as shaped by Te Tiriti o Waitangi/Treaty of Waitangi. Design/methodology/approach: This paper frames Te Tiriti as a structural attractor for social innovation in Aotearoa-New Zealand and explores the dynamics at play in the social and economic activities related to Te Tiriti and the ongoing settlement process in Aotearoa-New Zealand. This paper outlines this as an illustrative case study detailing the relevant contextual spaces and dynamics that interact and the emergence of social innovation. Findings: This paper suggests that the convergent, divergent and unifying dynamics present in a structural attractor provide a useful framework for building ongoing engagement between Indigenous and non-Indigenous people whereby Indigenous worldviews are given space to be articulated and valued. Originality/value: In spite of the increase in research into social innovation, including in Indigenous contexts, the "context" of "postcolonial" context remains under-theorised and people's understanding of the power dynamics at play here limits the understanding of how the mechanisms of Indigenous–settler partnerships structure social innovation and its impact.